An Investigation of the Scottish Judicial System in the Light of the 2005 Constitutional Reforms - MAMMERINE, Mohammed Ali; MACHANA, Oussama (University of Eloued جامعة الوادي, 2024)
This research attempts to conduct an analytic study in order to investigate the impact of the 2005 Constitutional Reforms on the Scottish Judicial System. The significance of this research lies in the fact that despite Scotland, as a part of the United Kingdom, bases its political system on the separation of power, the role of the Lord Chancellor as a member of the three branches of power could undermine the independence of its local Judiciary. In order to conduct this study, three questions have been raised. The first question raises concerns on the role of the Scottish Legal System as a subordinate to the Executive before 2005. The second question investigates how the 2005 reforms have strengthened Scotland Judiciary. The third question asks whether these reforms have settled balance amongst the branches of power.To respond to these questions, three hypotheses have been formulated .The first hypothesizes relates between the laws preceding the reforms and Scotland Judiciary dependence on the Executive. The second hypothesizes that the adoption of the 2005 Constitutional Reforms could lead to an independent Scottish Judicial System .The third assumes that the reforms could have no effect on the Scottish Legal System. In order to investigate the validity of these hypotheses, the study used the historical-analytical method by analyzing the relevant documentary sources. The findings of the study revealed that the Scottish Judiciary System, before the Constitutional Reforms, was weak and controlled by the Lord Chancellor as a member of the Executive and Head of the House of Lords. The Constitutional Reform Act 2005 brought radical changes, including the establishment of a Supreme Court, the abolishment of the House of Lords' jurisdictional power. On the other hand, it contributed to the weakening of the power of the Lord Chancellor, and the creation of an independent Judicial Appointments Commission. Consequently, the Scottish Legal System became more independent and more powerful. يسعى هذا البحث إلى إجراء دراسة تحليلية من أجل التحقيق في النظام القضائي الأسكتلندي في ضوء الإصلاح الدستوري لعام 2005 من أجل إجراء هذه الدراسة، طُرحت ثلاثة أسئلة. ويتناول السؤال الأول السمات التي يتسم بها النظام القضائي الأسكتلندي قبل عام 2005. وتتناول الثانية النظام القضائي الأسكتلندي بعد عام 2005 من النظام القضائي السابق على الإصلاح. وللإجابة على الأسئلة السابقة، تم صياغة ثلاث فرضيات. تقترح الفرضية الأولى أن اعتماد الإصلاح الدستوري لعام 2005 يمكن أن يؤدي إلى استقلال النظام القضائي، والحفاظ على نظام قانوني قضائي قوي ;إلى أن خصوصيات قانون الإصلاح الدستوري لعام 2005 يمكن أن تحدث تغييرات جذرية في النظام القضائي من حيث هيكل المحاكم والوظائف وتعيين القضاة. أما الفرضية الثالثة فتنص على أن اعتماد قانون الإصلاح الدستوري لعام 2005 يمكن أن يمنح السلطة والسلطة للسلطة القضائية. ومن أجل التحقق من صحة فرضياتنا، استخدمنا الأساليب التحليلية التاريخية والمقارنة. كشفت نتائج الدراسة أن النظام القضائي الأسكتلندي، قبل الإصلاحات الدستورية، كان ضعيفا وتخضع لسيطرة السلطات الواسعة للسيد المستشار. وبعد التحليل تبين بالتغييرات جدرية قد حصلت في النظام القضائي الأسكتلندي منها هيكلة المحاكم. وإنشاء محكمة عليا منفصلة، إلغاء السلطة القضائية لمجلس اللوردات، تعديل دور اللورد المستشار ومكتبه، إضافة إلى إنشاء لجنة تعيينات قضائية مستقلة، ونتيجة لذلك فقد أصبح النظام القضائي في اسكتلندا أكثر قوة واستقلالية وذا سلطة و نفوذ على غير ما كان عليه سابقا.
Keywords: The Constitutional Reform Act - The Judiciary - Lord Chancellor - The Scottish legal System; مجلس اللوردات، اللورد المستشار; القضاء; قانون الاصلاح الدستوري